Experiences of a London Medical Student in the COVID-19 Pandemic - Suseanu, Alin-Ioan (International Journal of Medical Students, 2020)
The COVID-19 pandemic has changed life as we know it. As a senior medical student in London, I offer my perspective on how the virus has affected my education and the potential impact on the education of future medical students. I cover topics including videoconferencing replacing clinical placements, the disadvantages of online learning and an unprecedent shift to online, open book examinations.